2021
DOI: 10.1177/21501327211041862
|View full text |Cite
|
Sign up to set email alerts
|

Learning From Cervical Cancer Survivors: An Examination of Barriers and Facilitators to Cervical Cancer Screening Among Women in the United States

Abstract: Background: Screening and timely follow-up have lowered cervical cancer incidence in the US; however, screening coverage, incidence, and death rates have remained fairly stable in recent years. Studies suggest that half of women diagnosed with cervical cancer don’t receive appropriate screening prior to diagnosis; cervical cancer survivors can provide crucial insight into barriers and facilitators to screening. Methods: Participants were cervical cancer survivors ≥21 years, identified through population-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Additionally, we observed that cervical cancer survivors had slightly lower screening use (65%) compared to other types of cancer survivorships. Compared to a prior study, using cancer registries, 78% of cervical cancer survivors received CRC screening [ 32 ]. Higher screening use from this study may be due to using registry-based data, which usually have more accurate information compared to self-reported data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we observed that cervical cancer survivors had slightly lower screening use (65%) compared to other types of cancer survivorships. Compared to a prior study, using cancer registries, 78% of cervical cancer survivors received CRC screening [ 32 ]. Higher screening use from this study may be due to using registry-based data, which usually have more accurate information compared to self-reported data.…”
Section: Discussionmentioning
confidence: 99%
“…Higher screening use from this study may be due to using registry-based data, which usually have more accurate information compared to self-reported data. Variations of CRC screening utilization across different cancer types may be influenced by doctor’s recommendations on screening tests [ 23 ] and CRC risk perceptions [ 33 , 34 ] as well as insurance coverage to access preventive care [ 32 , 35 ]. Finally, more research on examining CRC screening behaviors in skin and lung cancer survivors are needed due to lack of existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…But whereas these approaches were recommended to increase equity in colorectal and breast cancer screenings, the recommendation was withheld for cervical cancer since evidence of effects on cervical cancer screening rates was lacking. Along similar lines, Senkomago et al’s ( 2021 ) comparison of screening barriers in women in a cancer registry and in a cancer survivors’ social network ( Cervivor ) found the barrier “Clinic hours were inconvenient” to be among the least common responses—though more common among the study’s racially diverse and socioeconomically disadvantaged social network cohort. Interestingly, in the same study, one of two most common facilitators of screening in the social network group was “Having screening tests with their annual exams,” suggesting that clinic hours might only partially capture the scheduling construct (Senkomago et al, 2021 ).…”
Section: Discussionmentioning
confidence: 80%
“…Along similar lines, Senkomago et al’s ( 2021 ) comparison of screening barriers in women in a cancer registry and in a cancer survivors’ social network ( Cervivor ) found the barrier “Clinic hours were inconvenient” to be among the least common responses—though more common among the study’s racially diverse and socioeconomically disadvantaged social network cohort. Interestingly, in the same study, one of two most common facilitators of screening in the social network group was “Having screening tests with their annual exams,” suggesting that clinic hours might only partially capture the scheduling construct (Senkomago et al, 2021 ). Mkuu et al’s ( 2022 ) study of clinicians’ views of cervical care barriers for women with behavioral health conditions (i.e., mental health and substance use) adds another perspective: in the clinicians’ view, the salient scheduling barrier was women’s “forgetting” to schedule appointments, not the availability or lack of ease in making appointments.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation